Evaluation of Bacterial Biofilm as Biosensor for Detecting Phenol, Catechol, and 1,2-dihydroxynaphthalene - Dyah Iswantini; Ali Aulia Ghozali; Cecep Kusmana; Novik Nurhidayat (Bogor Agricultural University, Indonesia, 2021)
Monitoring of water quality from the presence of polyaromatic hydrocarbon (PAHs) compounds and its derivates are important for keeping the healthy aquatic environment. Some of those derivates are phenol and several related compounds sharing simmilar structures. This reseach aimed for the detection of those phenol and several similar compounds monitoring due to PAHs degradation. Three identified bacterial isolates of Pseudomonas aeruginosa, Staphylococcus sciuri, and Bacillus amyloliquifaciens were selected based on their phenol degradation characters. On physiological properties all three isolates were observed to degrade several hydrophobic substances such as for naphthalene and anthracene. Yet, genetic analysis indicated that the phenolic degradating oxygenase gene was detected only in the P. aeruginosa and S. sciuri. Applying those isolates for biofilm as biosensor showed a sufficient analytical performance such as their limit of detection between 0.1-0.5 μM.